No evidence of autoimmunity to human OX1 or OX2 orexin receptors in Pandemrix-vaccinated narcoleptic children - Krister Melén; Pinja Jalkanen; Jyrki P. Kukkonen; Markku Partinen; Hanna Nohynek; Arja Vuorela; Outi Vaarala; Tobias L. Freitag; Seppo Meri; Ilkka Julkunen (Elsevier B.V., 2022)
Narcolepsy type 1, likely an immune-mediated disease, is characterized by excessive daytime sleepiness and cataplexy. The disease is strongly associated with human leukocyte antigen (HLA) DQB1∗06:02. A significant increase in the incidence of childhood and adolescent narcolepsy was observed after a vaccination campaign with AS03-adjuvanted Pandemrix influenza vaccine in Nordic and several other countries in 2010 and 2011. Previously, it has been suggested that a surface-exposed region of influenza A nucleoprotein, a structural component of the Pandemrix vaccine, shares amino acid residues with the first extracellular domain of the human OX2 orexin/hypocretin receptor eliciting the development of autoantibodies. Here, we analyzed, whether H1N1pdm09 infection or Pandemrix vaccination contributed to the development of autoantibodies to the orexin precursor protein or the OX1 or OX2 receptors. The analysis was based on the presence or absence of autoantibody responses against analyzed proteins. Entire OX1 and OX2 receptors or just their extracellular N-termini were transiently expressed in HuH7 cells to determine specific antibody responses in human sera. Based on our immunofluorescence analysis, none of the 56 Pandemrix-vaccinated narcoleptic patients, 28 patients who suffered from a laboratory-confirmed H1N1pdm09 infection or 19 Pandemrix-vaccinated controls showed specific autoantibody responses to prepro-orexin, orexin receptors or the isolated extracellular N-termini of orexin receptors. We also did not find any evidence for cell-mediated immunity against the N-terminal epitopes of OX2. Our findings do not support the hypothesis that the surface-exposed region of the influenza nucleoprotein A would elicit the development of an immune response against orexin receptors.